2021
DOI: 10.1111/pedi.13247
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Caregivers' experience of pediatric type 1 diabetes: A qualitative study

Abstract: Objective It is widely recognized that Type 1 Diabetes (T1D) outcomes are worse among Hispanic children; however, little is published about the perspectives of these patients and their caregivers. Our intent was to characterize the lived experience of Hispanic caregivers of children with T1D, focusing on the role of language and culture and their perspectives on current medical care and alternative care models. We studied Hispanic caregivers of patients (age 2–17 years) with T1D of greater than 6 months' durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…A recent study reported the perspectives of Hispanic T1DM patients and their Hispanic caregivers [ 97 ]. The study highlighted some significant issues Hispanic caregivers faced while taking care of T1DM patients.…”
Section: Caregiving In Diabetesmentioning
confidence: 99%
“…A recent study reported the perspectives of Hispanic T1DM patients and their Hispanic caregivers [ 97 ]. The study highlighted some significant issues Hispanic caregivers faced while taking care of T1DM patients.…”
Section: Caregiving In Diabetesmentioning
confidence: 99%
“…3 Childhood chronic disease creates unique challenges and stressors for patients and families. 4 Type 1 diabetes is among the most common childhood chronic diseases, 4 with a substantial risk of mortality and morbidity. Successful treatment aims to reduce the risk of acute and chronic complications while preserving quality of life.…”
Section: Introductionmentioning
confidence: 99%